“It Takes More Than a Pill to Kill”: Bounded Accountability in Disciplining Professional Misconduct Despite Heightened Transparency - Kaynak, Ece; Rahman, Hatim A. (Organization Science, 2024)
Existing theory suggests that professionals are ineffective at regulating the work of their peers, especially when it comes to disciplining misconduct, because of professional norms of collegiality. In response, transparency measures have been put in place over the years to increase accountability toward key external audiences, such as the public, and to ensure that professionals hold guilty peers accountable for misconduct. Few studies, however, have sufficiently investigated how professionals discipline peer misconduct in the face of transparency measures. We gained access to a state medical board’s internal deliberations about how to discipline physicians guilty of overprescribing opioids, endangering public health. We found that even in the most egregious cases, the board predominantly refrained from implementing stringent disciplinary action despite extensive transparency measures. Our data allow us to theorize what we call bounded accountability, which refers to individuals charged with holding guilty actors accountable for their misconduct instituting only limited discipline. We found four mechanisms that constrained the exercise of accountability: information asymmetries between regulatory bodies, bureaucratic inefficiencies of the disciplinary apparatus, shared professional beliefs among decision makers, and interpersonal emotions between decision makers and the guilty professionals whom they are put in charge of disciplining. We found that these mechanisms operated at the field, occupational, organizational, and interpersonal levels, respectively. Utilizing a highly consequential study context, our findings suggest that when professional misconduct is disciplined by members of the same occupation, bounded accountability is the most likely outcome, even with extensive transparency measures in place. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.17932 .